1995
DOI: 10.1109/49.345873
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of LEO, MEO, and GEO global mobile satellite systems in the presence of interference and fading

Abstract: Several multisatellite and multispot systems have been recently proposed for provision of mobile and personal services with global coverage, adopting GEO or non-GEO (i.e., MEO, LEO) satellite constellations. The paper addresses an in-depth analysis of these constellations, evaluating both geometrical performance measures and cochannel interference levels caused by extensive frequency reuse. The geometrical analysis yields the statistics for coverage, frequency of satellite hand-overs, and link absence periods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(89 citation statements)
references
References 10 publications
1
88
0
Order By: Relevance
“…In the case where the satellites are in close proximity within the main lobe of the receiving ground station antenna, long periods of interference between the two satellites can manifest itself. During these periods, the downlink of the adjacent satellites may be severely impaired [6]. Three pairs of operational SARSAT satellites are susceptible to this interference condition: S10/S12, S9/S11, and S7/S8 are identified and presented in Table 4 with their respective orbital periods and differences between them.…”
Section: Adjacent Satellitesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case where the satellites are in close proximity within the main lobe of the receiving ground station antenna, long periods of interference between the two satellites can manifest itself. During these periods, the downlink of the adjacent satellites may be severely impaired [6]. Three pairs of operational SARSAT satellites are susceptible to this interference condition: S10/S12, S9/S11, and S7/S8 are identified and presented in Table 4 with their respective orbital periods and differences between them.…”
Section: Adjacent Satellitesmentioning
confidence: 99%
“…It is shown that the supplemental use of both reduces the time delay and increases coverage area. Only LEOs adjacent interference is discussed [6]. …”
Section: Sarsat Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the contributions in [1,7,8,12,14] focus on hybrid coexistence scenario of satellite and terrestrial systems and the contributions in [6,9,11,13,15] address dual satellite coexistence scenarios. The interference scenario in a satellite system is different from that of the terrestrial systems due to the presence of the on-board antenna which acts as a spatial filter [2]. Cochannel interference mainly arises due to the presence of sidelobes in the on-board antenna radiation diagram i.e., non-ideal angular selectivity of the spotbeams.…”
Section: Introductionmentioning
confidence: 99%
“…GEO satellites utilize a circular orbit above the earth's equator maintaining the same position relative to the earth's surface whereas NGEO satellites generally have orbits with varying altitudes and positions. The main advantages of NGEO satellites are reduced free space attenuation, small propagation delay and the reduced cost of in-orbit injection per satellite [2]. Recently, the Others Three Billion (O3b) network has proposed to launch O3b satellites in the MEO of 8062 km in order to improve the round trip latency as compared to GEO orbit.…”
Section: Introductionmentioning
confidence: 99%